Proses Ekstraksi Asam Asetat dari Distilat Asap Cair Tempurung Kelapa Menggunakan Pelarut Etil Asetat - Faham Partogi Siregar, Rory; Misran, Erni; Tri Cahyadi, Iman (Jurnal Teknik Kimia USU, 2019)
Coconut shell is one of the most widely found biomass in Indonesia. It has potential to be utilized as raw material in producing liquid smoke. Liquid smoke is a distillate from pyrolysis of biomass. The distillate contains various compounds including acetic acid. This research is important to understand the effect of combined distillation and extraction on liquid smoke purificatian in obtaining acetic acid. The variation of solvent to feed ratio (2:1, 4:1, 6:1, dan 8:1) and temperature of extraction (30, 50, dan 70 Â°C) to obtain yield, acetic acid content, pH, and density which is the best among those of possible variable given. The objective of distillation is to separate the components with high boiling points such as tar. The main purpose of extraction is acetic acid recovery in order to obtain higher content of acetic acid in extract. The solvent in the process of extracting acetic acid is ethyl acetate. GC-MS analysis was also performed on this research to show composition of acetic acid from liquid smoke, distillate, and extract, which are all the composition of polar organic are also shown.